High resolution FTIR study of 34S16O2: Re-analysis of the bands ν1+ν2, ν2+ν3, and first analysis of the hot band2ν2+ν3-ν2; Journal of Molecular Spectroscopy; Vol. 319 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Sydow C.; Bauerecker (Bauerekker) Z. (S.) H. Zigurd (Sigurd) Hermann; Buttersack T. (2016, 2016)
Title screen